2005
DOI: 10.1007/s00234-005-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic signal changes in the pontine base on T2- and multishot diffusion-weighted images in spinocerebellar ataxia type 1

Abstract: The aim of the present study was to demonstrate characteristic signal changes of the pontine base on T2-weighted images of patients with SCA 1, and to elucidate the relationship between abnormal high-intensities of the pontine base on T2-weighted images and the findings on multishot diffusion-weighted images. We assessed abnormal signals of the pontine base on T2-weighted images from 50 controls and six patients with SCA 1 diagnosed by genetic analysis. At the same time, we evaluated the degeneration of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Nevertheless, none of the structural imaging markers taken into consideration separated SCA1 and SCA2. Midline hyperintensity in the pontine base was seen in all patients with SCA1, in accordance with a previous report by Adachi et al 24 However, because it was also found in 80% of patients with SCA2, it cannot serve as a differential diagnosis. The "cruciform sign," a typical feature of multiple system atrophy with cerebellar signs (MSA-C) reported to occur in advanced SCA2, was observed in 20% of patients with SCA1 as well.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, none of the structural imaging markers taken into consideration separated SCA1 and SCA2. Midline hyperintensity in the pontine base was seen in all patients with SCA1, in accordance with a previous report by Adachi et al 24 However, because it was also found in 80% of patients with SCA2, it cannot serve as a differential diagnosis. The "cruciform sign," a typical feature of multiple system atrophy with cerebellar signs (MSA-C) reported to occur in advanced SCA2, was observed in 20% of patients with SCA1 as well.…”
Section: Discussionsupporting
confidence: 91%
“…Adachi et al 24 studied patients with SCA1, SCA3, and SCA6 but assessed DWI images qualitatively only, without measuring the ADC and FA. Della Nave et al 15 compared SCA with other neurodegenerative diseases on the basis of ADC measurements but did not compare SCA1 and SCA2.…”
Section: Discussionmentioning
confidence: 99%
“…In general, on T2-weighted images no signal abnormalities are reported in the basal ganglia and the posterior fossa. There is only one report of a midline hyperintensity of the pontine base, which is not identical with the 'cross-sign', in 5 out of 6 SCA1 patients on T2-weighted changes (23). The significance and the specificity of this finding remain unclear at present.…”
Section: Sca1mentioning
confidence: 94%
“…Besides MSA‐C, HCBS has been reported in a few patients with SCA2 or SCA3 [7,8]. In one study [9], PMH has also been identified in six of the seven patients with SCA1 and two of the 50 healthy controls. A comprehensive investigation of the prevalence of HCBS and PMH in all SCA subtypes and healthy controls would help clarify their merit in the clinical practice.…”
Section: Introductionmentioning
confidence: 99%